STRUKTUR KEPRIBADIAN MANUSIA PERSPEKTIF PSIKOLOGI DAN FILSAFAT - Suhermanto Ja'far (Psympathic : Jurnal Ilmiah Psikologi, 2015)
Personality term refer to a principal that unite biological and social aspects. Personality defined differently by each psychological perspective. Freud with his psychoanalysis defined personality by hierarchy that consists of id, ego, and super ego. Alfred Adler as individual psychology theorist considered personality as medium that arranged facts and transform it into a personal and unique personality formed by self creativity. Jung with his analytical psychology suggested that personality or psyche is a dynamic with continually movement. Each personalilty aspect is required to complete an optimal differentiation and development level to achieve a healthy and integrated personality. Behaviorism considered behavior as main factor in defining personality. The personality components that consistent is the behavior it self. Humanistic psychology views personality as a union between body and soul which construct a historical awareness on its existence that point on an authentic and individual behavioural pattern.